Persepsi Terhadap Penggunaan Komunikasi Grafik Dalam Pengurusan : Satu Analisis Di Universiti Utara Malaysia - Nor Azli, Abdul Aziz (2002)
The rapid development in the technology has an enormous impact on graphics in the administration. This research attempts to evaluate the need and the importance of graphic to the departments in the Universiti Utara Malaysia (UUM) in achieving a world-class university. A total of 167 staffs from the support administrative groups I and II have participated in the research by answering the distributed questionnaires. The data is analyzed with one-way ANOVA and t-test. The findings proven that there is significant difference between the perception of the use of graphic in the UUM and age, sex, and educational backgrounds among the staffs. The data collection has assisted in guiding and providing basis for developing the use of graphic systematically. Finally, some implications and recommendations for future research will also be offered based on the findings of this research.